Shawn Schuler: capstone - Schuler, Shawn, artist (Colorado State University. Libraries, 2015)
The artist's statement: Within my studies as an undergraduate artist, I have predominantly expanded my horizons on dimensions and space. My primary Bachelor's degree is Electronic Art. However I am receiving another Bachelor in Landscape Design and Contracting with a Minor in Global Environmental Sustainability. With having both these degrees to refer to from the different colleges you can notice the influences from each design principle within my art. I utilizing pre-existing sites to reference and create scale model projects. I refer to prominent landscapes, historic architectural structures by representing them through digital fabrication methods and techniques. I have always been intrigued by representing projects with depth and complexity, in order to represent my reference or design as clearly as possible. Currently I use a 3-D modeling program called Rhinoceros 5, and use the epilog laser cutter to allow for precise cuts in order to assemble the models together accurately. Primarily I work with Baltic birch plywood on my models; however I have used acrylic Plexiglas, mat-board and cardboard to represent other projects. I enjoy the challenge of rebuilding an object from scratch to represent it in a smaller form in order for the viewer to comprehend the pieces scale in a more intimate setting. The more complex the design/project, the more I learn about problem solving and develop new methods and practices. For me, allowing the viewer to walk around the piece is more satisfying and is easier to grasp the information in front of them. My goal is to allow for the viewer to look at the actual object/place and have a moment of interaction with it, by walking around and viewing the piece from all angles. There is something unique to me about the reaction people get when they view a scaled object/site. I do not only specialize in digital fabrication, however I also enjoy painting abstract marble paintings by only utilizing one toothpick to create curvilinear forms and latex wall paint dripped into the large custom frames I built. I am a high believer in "doing it yourself" so anything I create a majority of the time is designed from scratch. I love problem solving and I believe you can find that within all my pieces.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art; sculpture; graphic design; painting; metalsmithing and jewelry